Low Platelet Count (Thrombocytopenia) in Females Diagnosed with Hypertensive Disorder after 20 Weeks of Gestation - Fareeha Ghaffar, Aasma Hanif, Asma Nawaz, Arjumand Mahmood, Shazia Noor, Tahira Rizwan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Platelets are produced in the bone marrow and remain in blood for about 2 weeks before they are destroyed in the reticuloendothelial system. The range of normal platelets count 150 & 450 × 103/μl that is also the same and is mostly recorded throughout the normal pregnancy. A platelet counts of less than 150 x103/μl is considered to be thrombocytopenia. It’s commonly diagnosed & has attracted interest from the1researchers in pregnant females during the last 20.0 years, especially in pregnant hypertensive women. Objective: To find frequency of low platelet count (thrombocytopenia)1in females diagnosed with hypertensive disorder after 20 weeks of gestation. Methodology Study Design: Cross sectional study Setting: Department of Obstetrics & Gynecology Shalimar hospital, Lahore. Material and Methods: All information was noted on attached proforma after getting written informed consent. From OPD of Department of Obstetrics and Gynecology Shalimar Hospital Lahore, a total of 282 females fulfilling selection criteria were taken. After enrolling the cases a detailed clinical assessment was done and their demographic and gestational information were taken along with parity. Pregnancy induced hypertension was further classified as Gestational HTN, Mild preeclampsia, Eclampsia and Severe preeclampsia. Blood sample with the help of staff nurse was drawn and was sent to hospital laboratory. Values of platelet count were noted after taking reports from hospital laboratory. Moreover using operational definition thrombocytopenia was labeled. Result: The mean age of cases was 30.68 ± 5.78 years with minimum and maximum age as 17 and 40 years. The mean gestational age was 31.74 ± 5.40 weeks with minimum and maximum gestational age was 22 and 40 weeks. A total of 235(83.33%) cases had thrombocytopenia and 47(16.67%) cases had normal platelet count. Conclusion: The conclusion of the study the frequency of low plate count (thrombocytopenia) in females diagnosed with hypertensive disorder after 20 weeks of gestation was 83.33%. The statistics is very high and there must be some preventive strategies to reduce the risk of hypertensive disorder, and if it once diagnosed the further therapeutic strategies should be adopted to reduce related complications such as thrombocytopenia. Keywords: Pregnancy, Thrombocytopenia, Gestational hypertension, Thrombocytopenia.